(untitled) (Journal of the College of Basic Education, 2022)
Wearing appropriate clothing grant respect for oneself, respect of others and promote a sense of self-confidence. Many factors intervene in the selection of appropriate clothing such as personality, and the event being attended , shape and body figure. Appearance depend on clothes more than the body shape , the body may seem smaller or larger than what it really seen ,by using the design elements, color , shape , line and texture of the clothes .